2017
DOI: 10.1016/j.ceramint.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

On-site Raman analysis of 17th and 18th century Limoges enamels: Implications on the European cobalt sources and the technological relationship between Limoges and Chinese enamels

Abstract: International audienceLimoges enamels on metal from the 17th to 18th centuries were analysed by non-invasive Raman microspectrometry with a mobile set-up in storage at the Musée des Arts Décoratifs (Paris) in order to identify the types of glazes and pigments used and to compare them with those found in Chinese cloisonné and falangcai enamels painted on metal and porcelain from the Kangxi and Yongzheng reigns (Qing dynasty). Certain French Jesuit and Chinese historical records report exchanges of technical kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 46 publications
5
66
0
Order By: Relevance
“…A similar feature was observed for the red garniture and carnation cheek of the lady (MNC 11234‐7, Figure b, right) and virgin (MNC 11234‐4, Figure c, right) figurines. This peak is characteristic of the As─O symmetric stretching mode arising from the arsenic ions used as a reducing agent for the precipitation of colloidal gold in the HNO 3 ─HCl mother mixture and then its dispersion of the resulting gold powder in the glassy matrix to obtain the ruby colour. Precipitation of colloidal gold with arsenic salt appears to be a characteristic of Perrot's methods whereas the Kunckel's method using precipitation with tin salts was more common in the 18th century production of ruby glass and Cassius purple glaze The narrow ~820 cm −1 peak is an indicator of the lead arsenate apatite phase Na 1 − x − 2y K x Ca y Pb 4 (AsO 4 ) 3 that is also formed by cooling on the reaction of cobalt ores containing arsenic (CoAs 2 , CoAs 3 , CoAsS, etc.…”
Section: Resultsmentioning
confidence: 99%
“…A similar feature was observed for the red garniture and carnation cheek of the lady (MNC 11234‐7, Figure b, right) and virgin (MNC 11234‐4, Figure c, right) figurines. This peak is characteristic of the As─O symmetric stretching mode arising from the arsenic ions used as a reducing agent for the precipitation of colloidal gold in the HNO 3 ─HCl mother mixture and then its dispersion of the resulting gold powder in the glassy matrix to obtain the ruby colour. Precipitation of colloidal gold with arsenic salt appears to be a characteristic of Perrot's methods whereas the Kunckel's method using precipitation with tin salts was more common in the 18th century production of ruby glass and Cassius purple glaze The narrow ~820 cm −1 peak is an indicator of the lead arsenate apatite phase Na 1 − x − 2y K x Ca y Pb 4 (AsO 4 ) 3 that is also formed by cooling on the reaction of cobalt ores containing arsenic (CoAs 2 , CoAs 3 , CoAsS, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of (a) an enamelled goblet (18th century Limoges Laudin family workshop) and (b) of a wucai Chinese porcelain vase using a high magnification (×200) long working distance (13 mm) microscope objective (see Colomban et al and Kirmizi et al for details); note the paper sheets used to protect from vibrations and to adjust the position of the spot in complement with the xyz stage; (b) the black textile covers the remote head and the artefact during the measurement…”
Section: Experimental and Proceduresmentioning
confidence: 99%
“…But the high toxicity of arsenic has limited the development of the technology. Recent on‐site studies of European soft‐paste porcelains and faience and of Limoges enamels demonstrated that lead arsenate was present in blue enamels. This arises from the use of cobalt arsenide to colour the glass, cobalt arsenides being the common mineral ores of the Erzgebirge mines in Saxony .…”
Section: Study Of Refractory (Inorganic) Materials—examplesmentioning
confidence: 99%
See 2 more Smart Citations